A test of the submentalizing hypothesis: Apes' performance in a false belief task inanimate control. Issue 4 (4th July 2017) - Krupenye, Christopher; Kano, Fumihiro; Hirata, Satoshi; Call, Josep; Tomasello, Michael
ABSTRACT: Much debate concerns whether any nonhuman animals share with humans the ability to infer others' mental states, such as desires and beliefs. In a recent eye-tracking false-belief task, we showed that great apes correctly anticipated that a human actor would search for a goal object where he had last seen it, even though the apes themselves knew that it was no longer there. In response, Heyes proposed that apes' looking behavior was guided not by social cognitive mechanisms but rather domain-general cueing effects, and suggested the use of inanimate controls to test this alternative submentalizing hypothesis. In the present study, we implemented the suggested inanimate control of our previous false-belief task. Apes attended well to key events but showed markedly fewer anticipatory looks and no significant tendency to look to the correct location. We thus found no evidence that submentalizing was responsible for apes' anticipatory looks in our false-belief task.